STUDY ON CO2 SOAKING TIME AND “HUFF AND PUFF” INJECTION CYCLE EFFECT IN TIGHT PERMEABILITY RESERVOIR - Muslim Abdurrahman; Fiki H. Ferizal; Dadan D.S.M. Saputra; Riri P. Sari (Testing Center for Oil and Gas LEMIGAS, 2019)
Oil and gas industry is struggling to improve oil production using several methods. CO2 injection is one of the advance proven technology to enhance oil production in numerous oil field in the world. Key parameters during CO2 injection are viscosity reduction and oil swelling which can improve oil production. CO2 injection also has high possibility to be applied in Indonesia's oil fields due to abundant CO2 sources surrounding oil fields. R field is one of reservoir candidates that appropriate for CO2 injection. It has a low pressure and low oil recovery due to low permeability (1-26,2 mD).The CO2 injection technique used in this study was huff and puff that consist of injection, shut in, and production phases. The simulation was conducted using compositional simulator. There were two parameters chosen to be analyzed, which were soaking time and injection cycle. The objective of this study is to know the CO2 huff and puff perfomance for improving oil recovery on low permeability reservoir. The result of the soaking time cases yields optimum condition in 21 days. For the case of injection cycle, the result for optimum condition is in 2 injection cycles. The recovery factor (RF) for both optimum condition reaches 22.96% from the baseline without gas injection (RF 5.82%).